1999
DOI: 10.1038/sj.bjc.6690064
|View full text |Cite
|
Sign up to set email alerts
|

p53 status of newly established acute myeloid leukaemia cell lines

Abstract: SummaryWe analysed the status of the p53 gene and protein in eight newly established acute myeloid leukaemia (AML) cell lines representing blast cells of either de novo leukaemia patients in first remission or patients with relapsed and chemotherapy-resistant disease causing their death. There were no mutations in the p53 gene in any of the cell lines as analysed by single-strand conformation polymorphism of amplified exons 5-8. However, the p53 protein was clearly and consistently expressed in all of these ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…It has been reported that both AML2 and AML3 cell lines contain wild-type p53 by nucleotide sequence analysis. 36,37 Anti-actin, -CDK9, -cyclin T1, -p53, -p21, -HDM2 and -NPM antibodies were purchased from Santa Cruz Biotechnology. Anti-Noxa, -Puma and -Survivin antibodies were obtained from Abcam.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that both AML2 and AML3 cell lines contain wild-type p53 by nucleotide sequence analysis. 36,37 Anti-actin, -CDK9, -cyclin T1, -p53, -p21, -HDM2 and -NPM antibodies were purchased from Santa Cruz Biotechnology. Anti-Noxa, -Puma and -Survivin antibodies were obtained from Abcam.…”
Section: Methodsmentioning
confidence: 99%
“…4,18 This was first observed in HL-60 cells that have a major rearrangement of p53 resulting in absence of p53 expression. 19 A number of groups have examined the occurrence of p53 alterations in various series of different types of hematopoietic cell lines derived from AML, 18,[20][21][22] T acute lymphoblastic leukemia (T-ALL), 23,24 B cell precursor-ALL (BCP-ALL), 25,26 B cell non-Hodgkin's lymphoma (B-NHL), [27][28][29] Burkitt's lymphoma 30,31 and myeloma. 32,33 We have undertaken a comprehensive analysis of the frequency of genomic p53 alterations in human malignant hematopoietic cell lines; data reported in the literature and our unpublished data are summarized in Figure 3.…”
Section: Higher Frequency Of P53 Alterations In Cell Lines Than In Prmentioning
confidence: 99%
“…4 Subsequent research has also shown that downstream p53 effector genes, such as p21, are rarely lost in AML and that wild-type p53 protein is expressed in newly established AML derived cell lines. 7 For this study, we measured several properties of p53 in primary AML cells, including TP53 gene sequence, per-cell abundance of p53 protein, and p53 phosphorylation at 5 residues. 8 Following DNA damage and cell stresses, p53 protein is rapidly phosphorylated at several residues, 9 including those we measured here (serines 15,20,37,46, and 392).…”
Section: Introductionmentioning
confidence: 99%